Microneedle System for Transdermal Drug and Vaccine Delivery: Devices, Safety, and Prospects - Xiaoxiang He; Jingyao Sun; Jian Zhuang; Hong Xu; Ying Liu; Daming Wu (SAGE Publishing, 2019)
Microneedle (MN) delivery system has been greatly developed to deliver drugs into the skin painlessly, noninvasively, and safety. In the past several decades, various types of MNs have been developed by the newer producing techniques. Briefly, as for the morphologically, MNs can be classified into solid, coated, dissolved, and hollow MN, based on the transdermal drug delivery methods of "poke and patch," "coat and poke," "poke and release," and "poke and flow," respectively. Microneedles also have other characteristics based on the materials and structures. In addition, various manufacturing techniques have been well-developed based on the materials. In this review, the materials, structures, morphologies, and fabricating methods of MNs are summarized. A separate part of the review is used to illustrate the application of MNs to deliver vaccine, insulin, lidocaine, aspirin, and other drugs. Finally, the review ends up with a perspective on the challenges in research and development of MNs, envisioning the future development of MNs as the next generation of drug delivery system.